Preliminary thermal evaluation of actuator for steer-by-wire vehicle - Mohd Azri Hizami, Rasid; Nurul Fatimah, Abdullah; Mohmad Sairaji, Muhamad Imran; A. R., Razali; Mohamad Heerwan, Peeie; Muhammad Izhar, Ishak; Ospina, Alejandro; Lanfranchi, Vincent (IEEE, 2018)
Automotive industry is moving towards electrification of steering system due to efficiency and active safety integration concerns. Studies on actuators for Steer-by-Wire (SBW) application is very limited, and no thermal effects on the actuator related to utilization in SBW have yet been looked into. Using a valid thermal model, and steer torque data collected from a journey mapping, a temperature profile of a prototype Synchronous Reluctance machine (Syncrel) has been established as if it was utilized as SBW actuator to verify the thermal robustness of the machine in that particular application. The maximum temperature in the winding is shown to not exceed the limit temperature for the winding insulation if the winding resistance can be divided by half of the current resistance in the prototype machine, thus, allowing us to consider Syncrel as another actuator solution for SBW.